Parenting stress and coping skils among single fathers and single mothers in east coast Peninsular Malaysia: A comparative study / Madihah Mohamad Shukri, Azlina Abu Bakar @ Mohd and Raja Zirwatul Aida Raja Ibrahim - Mohamad Shukri, Madihah; Abu Bakar @ Mohd, Azlina; Raja Ibrahim, Raja Zirwatul Aida (2004)
During recent years, the rate of single parent structure has increased steadily in Malaysian context and it provides a via alternative to nuclear family. Raising a child and managing life can be a stressful experience for single parents as they have no other parents to act as a buffer aid to share the responsibility with. Most of the previous research in Malaysia focused more on the problems and issues related to single mothers and its effect on the child well being. However, very little is known about the life of single fathers. The present research compared both single fathers and single mothers' parental stress and how they cope with the stress. 80 single fathers and 80 single mothers in Kota Bharu, Kuala Terengganu and Kuantan completed a set of questionnaire. The questionnaire comprises of sections on personal background, parenting stress and coping skills. The results highlight single father experience higher level of parenting stress compared to single mothers. There was no slightly difference between the way both single fathers and single mothers cope with stress. This indicate the fact more studies and programs should be more in tune with the issues related to single fathers besides single mothers.